DEVELOPING TRADITIONAL GAME BASED ENGLISH LEARNING MEDIA TO GROW LEARNING INTEREST OF JUNIOR HIGH SCHOOL STUDENTS - Dody Sugiarto; Agci Hikmawati (Journal of English Educational Study (JEES), 2019)
Abstract: The background of conducting this reseach began with the intention to develope an approprite English learning media for Junior High School students in the rural area by utilizing the traditional games. The seventh grade students of SMP N 1 Mendobarat, Bangka Regency academic year of 2018/2019 were involved as the population with 30 students as the samples taken by using purposive random sampling. In this Research and Development Research (R&D), the data were obtained from the distributed pre-test and post-test questionnaires. The procedures applied in this research were the one adopted from Lee and Owen (2004) with the following steps; analyzing students’ need by distributing the need analysis questionnaire, designing English learning media according to the data of need analysis, developing the first draft of the learning media, asking experts’ judgement, and validating it. Two kinds of test which were Alpha testing that involved material and content experts, and Beta testing that involved students were applied in the validation phase. Based on the finding of the research, it was found that the traditional games based English learning media was feasible to use by the seventh grade students of SMP N 1 Mendobarat, Bangka Regency. Therefore, this research leads to the recommendation to the students and teachers to consider traditional games as a feasible media to learn English.Key words: Traditional Game, Learning Media, English